High-light pronounced the effects of stocking density on photosynthesis and nutrients uptake of the bloom-forming green alga, Ulva linza - Bao, Menglin; Zhang, Qi; Xu, Zihan; Li, Baoqi; Wu, Hongyan; Zang, Shasha; Yan, Fang; Xu, Zhiguang; Liu, Ning (Frontiers in Marine Science, 2024)
In recent years, the periodic outbreak of green tides in the coastal areas of China, caused by the combined effects of environmental changes and human activities, has been attracting extensive attention due to the serious negative impacts on the coastal marine ecosystem. In the study, the samples of Ulva linza, a green tide species, were cultivated under two light intensities (LL: 80 μmol photons m-2 s-1; HL: 300 μmol photons m-2 s-1) and three stocking densities (LD: 0.2 g L-1; MD:1 g L-1; HD:2 g L-1) to explore the photosynthetic physiological responses and nutrients absorption capacity. The results showed that high light and low density significantly increased the growth rate of U. linza. Under the HLLD, the maximum growth rate of U. linza was 43.13% day-1 and the energy captured per unit reaction center for electron transfer (ET0/RC) was the highest. The higher density significantly decreased the maximum relative electron transfer rate (rETRmax) of U. linza, especially among groups subjected to high-light condition. Under HL condition, HD also significantly decreased light utilization efficiency (α) in U. linza. The contents of chlorophyll a, b and carotenoids of U. linza were significantly lower in HLLD group compared to other treatment groups. The P uptake of U. linza was prominently inhibited by higher density, and the maximum P uptake and minimum P uptake was 17.94 μM g-1 FW day-1 in LLLD group and 2.74 μM g-1 FW day-1 in LLHD group, respectively. Lower density improved N uptake of U. linza, but high light had no effect on it. These results suggest that high light and lower density synergistically promote the growth of U. linza, which is likely due to enhanced photosynthetic efficiency and nutrient uptake. And the inhibitory effects of higher densities on growth, particularly under high-light conditions, may be due to increased competition for light and nutrients. In the late stage of the green tides outbreak, an increase in accumulation density could help to suppress the sustained outbreak of the green tides, particularly in high-light condition.